PENGELOLAAN PIUTANG SIMPAN PINJAM PADA KOPERASI HIDAYAH SAMARINDA - Tobing, Vina Agustina (EKONOMIA, 2014)
Hidayah Cooperative is a cooperative whose main activity was to accept deposits from members, and channel them back to members who need a loan to open up and increase its business in the form of short-term credit. Cooperative Hidayah established only four years, during the four years of the establishment of the system used is still very simple and has several drawbacks. in order to manage the accounts properly will require adequate internal controls, in order to assess the suitability of the implementation of the standards and established procedures, and tools that can be used to ensure the appropriateness and effectiveness of operational activities support the realization of receivables management is an internal audit. Formulation of the problem in this study is "Is the management activities of savings and loan receivables are comprised of cash receipts system of installment credit and credit cooperative system has Hidayah are conducted in accordance with standards and procedures have been established? ". The hypothesis in this study is "that the implementation of savings and loans receivable management activities are comprised of cash receipts system of installment credit, and the credit system has not been implemented at Hidayah cooperative in accordance with the standards and procedures have been established". The analytical tool used is to use internal audit stages, namely preliminary stage, review and testing of management control, detailed auditing, reporting, and follow-up. The results showed that the implementation of the management of cooperative savings and loan receivables Hidayah still not implemented in accordance with the standards and procedures established. The findings obtained during the audit process is the double post, no written rules governing both the maturity payment, document use cash receipts, and credit, do not deposit cash into the bank, the absence of rotation position, the absence of authorization for each activity, and did not assess the effectiveness of the provision of credit. The findings above indicate that the hypothesis is accepted.